The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1002/chin.200716022
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Organic Compounds over NaBiO3 under Visible Light Irradiation.

Abstract: Catalysts H 2000Decomposition of Organic Compounds over NaBiO3 under Visible Light Irradiation. -The title compound is prepared by heating NaBiO 3 ·nH 2 O in air at 413 K for 5 h and characterized by XRD, UV/VIS diffuse reflectance spectroscopy, and DFT electronic structure calculations. The samples crystallize with ilmenite type structure in the space group R3. Decomposition experiments of gaseous 2-propanol and methylene blue in the liquid phase indicate that NaBiO3 is a promising material for photooxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 1 publication
0
24
0
Order By: Relevance
“…It is noted that the composition of NaBiO 3 valance band is very different from other Bi-containing semiconductor compounds, such as Bi 2 WO 6 [19] and BaBiO 3 [14]. According to the density of states (DOS) analysis of NaBiO 3 [15], broad valence band (VB) was mainly composed of the O 2p orbital owning to the empty Bi 6 s and Na 3 s orbitals. For the reaction [20]: In addition, the band edge of NaBiO 3 semiconductor at the point of zero charge was calculated by the equation as follows:…”
Section: Photocatalytic Degradation Mechanismmentioning
confidence: 98%
See 2 more Smart Citations
“…It is noted that the composition of NaBiO 3 valance band is very different from other Bi-containing semiconductor compounds, such as Bi 2 WO 6 [19] and BaBiO 3 [14]. According to the density of states (DOS) analysis of NaBiO 3 [15], broad valence band (VB) was mainly composed of the O 2p orbital owning to the empty Bi 6 s and Na 3 s orbitals. For the reaction [20]: In addition, the band edge of NaBiO 3 semiconductor at the point of zero charge was calculated by the equation as follows:…”
Section: Photocatalytic Degradation Mechanismmentioning
confidence: 98%
“…Bi-containing oxides such as Bi 2 Ti 2 O 7 [11], Bi 2 WO 6 [12,13] and BaBiO 3 [14] have been reported to be promising photocatalysts under visible light irradiation. NaBiO 3 is another new efficient photocatalyst which was firstly demonstrated by Tetsuya Kako et al Their results show that NaBiO 3 showed a higher photocatalytic activity towards methylene blue compared to some other visible light sensitive semiconductor compounds such as N doped TiO 2 and BiVO 4 [15]. To the best of our knowledge, however, a systematic study based on photocatalytic performance research of NaBiO 3 has not been reported so far.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, it is very important to develop visible light-sensitive photocatalyst, which can efficiently utilize inexpensive and inexhaustible solar energy. NaBiO 3 is a new efficient photocatalyst [10], which was firstly reported by Kako et al Their results indicate that NaBiO 3 showed a higher photocatalytic activity towards methylene blue compared to some other visible light-sensitive semiconductor compounds, such as N doped TiO 2 and BiVO 4 . Takei et al [11] studied the photocatalytic behavior of some bismutates with Bi 5+ and found that NaBiO 3 showed the highest activity for phenol decomposition among nine Bi 5+ photocatalysts.…”
Section: Introductionmentioning
confidence: 86%
“…Recently, a number of Bi-based photocatalysts, such as NaBiO 3 [16], Bi 3 O 4 Cl [17], Bi 4 Ti 3 O 12 [18] and Bi 2 WO 4 [3], were synthesized; these materials showed high photocatalytic activities even under visible light irradiation. It seems that bismuth maybe a proper candidate dopant element to extend the TiO 2 spectral response and thus to improve its photoreactivity.…”
Section: Introductionmentioning
confidence: 99%